PERSEPSI MAHASISWA PENDIDIKAN DOKTER FAKULTAS KEDOKTERAN UNIVERSITAS GADJAH MADA TERHADAP PENGGUNAAN MANIKIN DI DALAM BELAJAR KETERAMPILAN KLINIK DI SKILLS LAB - , SYAMSUL RIZAL ([Yogyakarta] : Universitas Gadjah Mada, 2014)
BACKGROUND :Mannequin is one of the many methods in Skills Laboratory Learning. Mannequin is the first step in Skills Lab. learning system before the students take a practice with their friends. The last step is taking a part in the society. If the mannequin is broken, it will affect the learning system in Skills Lab. It has a relationship with students learning motivation. OBJECTIVES :This study is aimed to know studentsâs perception about the mannequin in Skills Lab. and to know studentâs suggestion about it. METHOD :The method of this study is qualitative research. Data is collected by interviewing the students of FK UGM. RESULTS :There are 16 mannequins which are analyzed by the researcher and almost all of the students feel satisfied with the mannequin. CONCLUSION :The factors that affect students satisfaction is: 1). The shape resemblance of mannequin. 2) The consistency resemblance of mannequin. 3). The function of mannequin. 4.) The trace which is left by the later using.